Using decision support systems for transportation planning efficiency - Ocalir-Akunal, Ebru 1972- (Advances in civil and industrial engineering (ACIE) book series, 2016)
This book is a valuable reference source of the latest scholarly research on the vast improvements that computational innovations have made for transportation planners, featuring extensive coverage on a range of topics relating to spatial planning, environmental risks of transport, and traffic information systems"--Provided by publisher